Reporting Back: U.S. ELAM Students Return from their Summer BES Projects - Joanna Mae Souers (Social Medicine Publication Group, 2009)
During the summer of 2009, 19 students of the U.S. delegation from the Latin American School of Medicine (Spanish acronym ELAM), in Havana, Cuba, participated in the Brigadas Estudantil de Salud (BES), launching two student groups; the ¡Salud! Southwest Exchange and the ¡Salud! New Orleans Project. Now, Joanna Mae Souers, one of the principle organizers of the Salud Southwest Exchange and 3rd year student at ELAM, reports back on behalf of the students' summer of success.